Vulval lichen sclerosus: An Australasian management consensus. (12th June 2021) - Yeon, Janice; Oakley, Amanda; Olsson, Ann; Drummond, Catherine; Veysey, Emma; Marshman, Gillian; Saunders, Helen; Opie, Jacinta; Bradford, Jennifer; Cole, Judith; DeAmbrosis, Kate; Cook, Kathryn; et al.
Abstract: Background/Objectives: Vulval lichen sclerosus (VLS) is a chronic inflammatory skin condition predominantly affecting the anogenital region in women and children. To date, there is lack of agreement amongst experts on a severity scale to aid assessment, research and treatment stratification on VLS. Furthermore, literature on best practice for long‐term management of VLS is lacking. The aim of this consensus is to provide broad guidelines on the short and long‐term management of VLS. Methods: An initial focus group of Australasian experts in vulval dermatology developed a draft consensus statement for the management of VLS. Based on the results of the draft statement, a consensus panel of 22 Australasian experts, comprised of the initial and additional members, participated in an anonymous four‐stage eDelphi process. Round 1 involved generation and voting on statements from the draft consensus statement developed by the focus group. In Rounds 2, 3 & 4, panel members were presented formal feedback from previous rounds and asked to indicate their level of agreement. Consensus was reached if there was ≥70% agreement on the importance of an item in the 4 (agree) to 5 (strongly agree) range. Results: The expert panel, with a total of 504 collective years of experience in the field of VLS, reached consensus on a core set of 51 management statements related to diagnosis, severity, initial and long‐term management, follow‐up, and complications of VLS. Conclusions: This study has identified a set of management statements for VLS that may be useful in clinical practice in the Australasian population.